Liver iron concentration and liver impairment in relation to serum IGF-1 levels in thalassaemia major patients: A retrospective study - Vincenzo De Sanctis; Ashraf T Soliman; Giancarlo Candini; Christos Kattamis; Giuseppe Raiola; Heba Elsedfy (Mediterranean Journal of Hematology and Infectious Diseases)
Not available